Optical Active Meta-Surfaces, -Substrates, and Single Quantum Dots Based on Tuning Organic Composites with Graphene - Romero, Marcelo R.; Bracamonte, A. Guillermo (2024)
Impact Factor (IF) - 2023 (2024 update): 3.1